Preference Direction Study of Sai Oua by External Preference Mapping and Modified Ratio Profile Test - Wiwat Wangcharoen; Napaporn Deesanam; Thanes Keokamnerd; Umaporn Siripin (Agriculture and Natural Resources, 2006)
To study the preference direction of consumers of the Thai traditional Northern-style sausage, Sai Oua, this study selected four products from fresh markets in Chiangmai and a fifth product was produced by the reseaech team. External preference mapping showed that 100 Thai consumers could be clustered into 2 main groups by preference direction. The first preference direction group preferred products which were high in tenderness and juiciness, but less in undesirable meaty and rancid flavours, whilst the second group preferred products which were high in curry paste, lemongrass, and bergamot leaf flavours, but less in saltiness. The result of modified ratio profile test also showed that another group of 100 Thai consumers could be clustered into 2 main groups. The first group preferred products which were high in tenderness, juiciness, and intensity of curry paste, but moderate in lemongrass and bergamot leaf flavours and saltiness, and low in undesirable meaty and rancid flavours. Another group preferred products which were very high in curry paste, lemongrass, and bergamot leaf flavours, tenderness, and juiciness, and low in undesirable meaty and rancid flavours. Even though the results of both methods were not exactly similar, some agreements were found.